Design and Simulation of Low Circadian Action Micro-LED Displays with Four Primary Colors - Ziqian He; Guanjun Tan; Yi-Fen Lan; Shin-Tson Wu (Crystals, 2020)
Nowadays, displays are ubiquitous in our daily lives. Long-time exposure to a display’s unnatural light could influence the user’s circadian rhythm, especially at night. Here, we propose a four-color micro-light-emitting diode (LED) display to achieve low circadian action for nighttime uses. Specifically, we evaluate the RGBW-type (red, green, blue, and white) and RYGB-type (red, yellow, green, and blue) micro-LED displays in terms of circadian effect and color gamut coverage. With the addition of an extra white subpixel, it was found that the circadian effect at night can be reduced dramatically, but the color gamut remains unchanged. However, with an additional yellow subpixel, both the circadian effect and color gamut were found to improve. Finally, we simulated the circadian illuminance of real image contents for different displays. In comparison with existing liquid crystal displays, organic LED displays, and RGB (red, green, blue) micro-LED displays, the proposed four-primary-color micro-LED displays can significantly reduce the circadian effect at night.